Hydrogen Peroxide Is Responsible for the Cytotoxic Effects of Streptococcus pneumoniae on Primary Microglia in the Absence of Pneumolysin - Franziska Jennert; Désirée Schaaf; Roland Nau; Thomas P. Kohler; Sven Hammerschmidt; Darius Häusler; Peter Valentin-Weigand; Jana Seele (Karger Publishers, 2024)
Introduction: Streptococcus pneumoniae is the most common cause of bacterial meningitis and meningoencephalitis in humans. The bacterium produces numerous virulence determinants; among them, hydrogen peroxide (H2O2) and pneumolysin (Ply) contribute to bacterial cytotoxicity. Microglia, the resident phagocytes in the brain, are distinct from other macrophages, and we thus compared their susceptibility to pneumococcal toxicity and their ability to phagocytose pneumococci with those of bone-marrow-derived macrophages (BMDMs). Methods: Microglia and BMDMs were co-incubated with S. pneumoniae D39 to analyze the survival of phagocytes by fluorescence microscopy, bacterial growth by quantitative plating, and phagocytosis by an antibiotic protection assay. Ply was detected by hemolysis assay and Western blot analysis. Results: We found that microglia were killed during pneumococcal infection with a wild-type and an isogenic ply-deficient mutant, whereas the viability of BMDMs was not affected by pneumococci. Treatment with recombinant Ply showed a dose-dependent cytotoxic effect on microglia and BMDMs. However, high concentrations of recombinant Ply were required, and under the chosen experimental conditions, Ply was not detectable in the supernatant during infection of microglia. Inactivation of H2O2 by exogenously added catalase abolished its cytotoxic effect. Consequently, infection of microglia with pneumococci deficient for the pyruvate oxidase SpxB, primarily producing H2O2, resulted in reduced killing of microglia. Conclusion: Taken together, in the absence of Ply, H2O2 caused cell death in primary phagocytes in concentrations produced by pneumococci.